Eksplorasi Peran Gaya Kepemimpinan Transformasional Dalam Membangun Budaya Organisasi Positif Di PT. Inspira Energi Sekawan - Marwan, Benaya Aushaf Razan Putra; Fauzi, Achmad; Wahyu S, Novita; Hasanuddin; Sari, Rycha Kuwara (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Inspira Energi Sekawan is a company engaged in the supply of cables. This study was conducted to determine the role of transformational leadership in building organizational culture at PT. Inspira Energi Sekawan. This study used qualitative methods with data collection techniques involving field observations, interviews with informants, and documentation. The findings from the interviews with informants, as noted in the observation records under the sub-focus on discipline, revealed several strengths in the observation findings. Specifically, the company leaders have implemented strict regulations, provided constructive suggestions for various issues, and fostered a healthy two-way communication culture